Diffusivities of Ternary Mixtures of n-Alkanes with Dissolved Gases by Dynamic Light Scattering - Heller, Andreas; Giraudet, Cédric; Makrodimitri, Zoi A.; Fleys, Matthieu S. H.; Chen, Jiaqi; van der Laan, Gerard P.; Economou, Ioannis G.; Rausch, Michael Heinrich; Fröba, Andreas Paul (Journal of Physical Chemistry B, 2016)
Theoretical approaches suggest that dynamic light scattering (DLS) signals from low-molecular-weight ternary mixtures are governed by fluctuations in temperature as well as two individual contributions from fluctuations in concentration that are related to the eigenvalues of the Fick diffusion matrix. Until now, this could not be proven experimentally in a conclusive way. In the present study, a detailed analysis of DLS signals in ternary mixtures consisting of n-dodecane (n-C12H26) and n-octacosane (n-C28H58) with dissolved hydrogen (H-2), carbon monoxide (CO), or water (H2O) as well as of n-C12H26 or n-C28H58 with dissolved H-2 and CO is given for temperatures up to 523 K and pressures up to 4.1 MPa. Thermal diffusivities of pure n-C12H26 and n-C28H58 as well as thermal and mutual diffusivities of their binary mixtures being the basis for the ternary mixtures with dissolved gas were studied for comparison purposes. For the investigated ternary mixtures, three individual signals could be distinguished in the time-resolved analysis of scattered light intensity by using photon correlation spectroscopy (PCS). For the first time, it could be evidenced that these signals are clearly associated with hydrodynamic modes. In most cases, the fastest mode observable for ternary mixtures is associated with the thermal diffusivity. The two further modes obviously related to the molecular mass transport are observable on different time scales and comparable to the modes associated with the concentration fluctuations in the respective binary mixtures. Comparison of the experimental data with results from molecular dynamics simulations revealed very good agreement.